CORRELATION OF DEPRESSION AND DAILY LIFE: HOW DEPRESSION AFFECTS QUALITY OF LIFE - Helga Puspita (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2023)
Depression is one of the most common mental disorders in the world and can have a huge impact on a person's daily life. Research has shown that depression can affect a person's general quality of life, as well as a person's ability to carry out daily activities such as working, studying, and getting along with other people. Depression can also hurt one's relationships with others, especially in terms of communication and social interaction. This study aims to present a detailed review of how depression can affect one's daily life and how one can overcome depression to improve one's quality of life. This article outlines the causes of depression, the signs and symptoms of depression, and the various treatments available for depression. The method used in this study is a literature review. The results showed that there was a significant correlation between the level of depression and a person's quality of life. People suffering from depression tend to have a lower quality of life. In conclusion, depression can affect a person's daily life significantly and it is important to know the signs and symptoms of depression and how to deal with it to improve the quality of life of someone suffering from depression.